Energy-Harvesting Mechanisms for UAV Flight by Dynamic Soaring. Issue 3 (September 2015) - Bonnin, V.; Benard, E.; Moschetta, J.-M.; Toomer, C. A.
Dynamic Soaring is a flying technique which extracts energy from an environment where wind gradients form, with the potential to increase the endurance of small unmanned vehicles. The feasibility to use dynamic soaring flight is questioned here; it requires the identification of energy-extraction mechanisms as well as accurate understanding of the way energy-harvesting performances are governed by trajectory constraints, vehicle characteristics and environment conditions. A three-dimensional energy-neutral trajectory is derived out of a specified optimization problem. Characteristic phases of flight are evidenced out of an overall closed trajectory. Simplified equations are used to evidence the physics behind energy transfers. Finally, overall energy-harvesting balance is studied through local variations of total energy along the path.